Penerapan Kompetensi Sosial Guru Kelas dalam Proses Pembelajaran di SD Negeri 71 Banda Aceh - Atira Oftafia; Alfiati Syafrina; Ahadin Ahadin (Universitas Syiah Kuala, 2022)
This study aims to describe the application of classroom teacher social competence in the learning process at SD Negeri 71 Banda Aceh. The approach taken is qualitative with a descriptive type of research. The subjects in the study were 6 class teachers, 1 principal, and 6 students. Data collection was done by observation and interviews. All data collected is processed by data analysis, namely data reduction, data presentation, and conclusion drawing. From the results of observations and interviews, there are problems with the 5 indicators of social competence, the six classroom teachers seem to have implemented several indicators of social competence and there are 2 indicators that are not visible and applied by teachers in the learning process, namely the indicators of communicating orally, in writing, and The indication is that there are teachers who do not use various methods and do not apply sign language in the learning process. As well as on indicators of using communication and information technology functionally, it can be seen that there are some teachers who do not use technology, in the use of technology, the lack of application of teachers is still mostly based on textbooks and does not use focus to support the learning process. In interacting with other teachers it is quite good but there is one teacher who does not apply it so communication is not good. The conclusions of this study indicate that the six class teachers of SD Negeri 71 Banda Aceh have implemented social competence in the learning process quite well. Therefore, teachers who have been seen in implementing social competence can maintain this